Prevalence of subclinical hypothyroidism in adults visiting primary health-care setting in Riyadh - Eidan Al Eidan; Saeed Ur Rahman; Saeed Al Qahtani; Ali I Al Farhan; Imad Abdulmajeed (Journal of Community Hospital Internal Medicine Perspectives, 2018)
Background and objectives: Subclinical hypothyroidism is an asymptomatic condition with normal thyroxin and raised thyroid stimulating hormone (TSH) level. The objective of the study was to determine the prevalence of subclinical hypothyroidism in primary health care (PHC) settings in Riyadh and explore the relationship of TSH level with age, gender, family history, body mass index, and co-morbid conditions. Subjects and methods: A cross-sectional study of adult visitors to nine satellites PHC clinics in military housing in Riyadh was carried out. TSH concentration and free T4 levels were measured. Data were collected by nurses and physicians during routine clinical practice in primary care. Descriptive analysis was performed on all variables in study, and relationships were explored using chi-square, t-test, analysis of variance, and linear regression. Results: A total of 340 out of 394 participants in the study gave blood samples. Subclinical hyperthyroidism was identified in 2.1% (p = .001) and subclinical hypothyroidism in 10.3% (p = .001) of the PHC visitors. TSH levels were found to be significantly higher (p = .047) in elderly population of ≥60 years and those with family history of thyroid disease. Non-significant upward trends were noted in TSH levels with hyperlipidemia and increasing blood pressure. No overt hyperthyroidism or hypothyroidism was found in our study sample. Conclusion: Subclinical hypothyroidism has a prevalence of 10% of adults visiting PHC’s. TSH levels are higher in the elderly, which warrants screening of those aged 60 years and above.